A Study of Modern Urdu Ghazal of Jammu and Kashmir: An Ecocritical Perspective - Gulzar Ahmed Sohil (Şarkiyat Mecmuası)
Jammu and Kashmir has a unique identity in the world because of its civilization, geographical structure and attractive natural scenery. This land has been very fertile in terms of knowledge and literature, having produced literary personalities like Kalhan, Sheikh Ul Alam, Lal Ded, Ghani Kashmiri, Allama Iqbal and countless others who have beautifully portrayed the various aspects of the nature of this land in their writings. In modern times, the voice of the environment is heard in every sphere of life but when anything makes presence in literature it has the greatest impact on society. When we study the modern Urdu ghazal of Jammu and Kashmir in the context of environmental criticism, we find that it is deep rooted in this land both on artistic and intellectual levels. In this ghazal, where on the one hand, attention has been paid to the sensitive environmental problems of modern times, including climate change, global warming, ecological balance, etc. On the other hand, the negative impact of environmental changes on natural capital can also be seen. Moreover, in these ghazals, where on the one hand the poets are seen fighting for the protection of the environment and civilization, on the other hand the ghazals also support the wilderness of nature and its free existence in order to raise the concept of environmental sensitivity among the people. These are the specific aspects of environmental literature.